Predict-Observe-Explain Strategy with Group Investigation Effect on Students’ Critical Thinking Skills and Learning Achievement (Journal of Primary Education, 2019)
This study aimed to identify the effect of Predict-Observe-Explain (POE) learning strategy with Group Investigation (GI) model on students’ learning achievement and critical thinking skills. The method used was Quasi Experimental Design type Control Group Pre-test – Post-test. Instrument for assessing learning achievement was test, while critical thinking skills were measured with observation sheets. Content and construct validity were used to make the instruments valid and reliable. Data analysis techniques used were independent t-test, one tail (right) test, N-gain test, analysis of observation sheet with checklist formula, and product moment correlation test. The study showed that the implementation of POE learning strategy with GI model had significantly effected students’ learning achievement and critical thinking skills. Data analysis showed tvalue was 73.42 which meant the experiment class had higher score than control class. N-gain mean score for experiment class was 0.18, meanwhile control class was 0.9. There were nine students’ critical thinking skill profiles which were showed significantly from the observation sheets. Critical thinking skills were also correlated significantly to students’ learning achievement. The implementation of POE strategy with GI model in providing benefits to train students to find their new knowledge, to improve their learning achievement and critical thinking skill, as well as to improve the quality of learning was discussed.